A Comparative Study: Attitudes and Thinking Patterns Students in Citizenship Education - Mardiana, Karfad; Mickovska-Raleva , Ana; Zakari, Jobila Mohammed (Journal of Social Knowledge Education (JSKE), 2024)
Purpose of the study: This study aims to explain the differences in attitudes and mindsets of grade XI students majoring in social sciences and grade XI students majoring in natural sciences in the subject of citizenship education. Methodology: The method used in this study is a descriptive method with a quantitative approach and data collection techniques using attitude scales and rubrics. The population in this study were students of grade XI majoring in social sciences and grade XI majoring in natural sciences at State Senior High School 1 Seputih Banyak, Central Lampung Regency, totaling 254 students with a sample taken as much as 20% of the population, namely 51 respondents. Main Findings: The results of the study showed that there was a significant difference between attitudes and mindsets with an average of 848 and 194.36 for grade XI students majoring in social sciences, while 868.67 and 219.99 for grade XI students majoring in natural sciences in the subject of citizenship education. This shows that grade XI students majoring in natural sciences have better attitudes and mindsets than grade XI students majoring in social sciences. Novelty/Originality of this study: The novelty of this study is the disclosure of significant differences in attitudes and mindsets between grade XI social science majors and grade XI natural science majors in the citizenship education subject, which provides new insights into how academic background influences their perceptions and approaches to citizenship education learning.